Development of the fixed-vane revolving vane compressor - Tan, Kok Ming (2012)
The dissertation deals with the development of a newly introduced positive displacement rotary compressor, named fixed-vane revolving vane compressor. The compressor design is conceived with the motivation for eliminating the dependency of the vane-side frictional loss on the working fluid pressures. Prediction shows that a reduction of frictional loss of 40% is achieved in one design and this has translated to 3.0% improvement in the coefficient of performance of the refrigeration cycle.